The Influence of the Mathemagics Method Assisted by Ice Cream Math Media on Understanding the Concept of Multiplication in Class 5 SDN Kowel 1 Pamekasan - Arofani, Lita; Sudi pratikno, Ahmad (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The background of this research begins with the researcher's observation of the mathematics learning process in class V SDN Kowel 1 Pamekasan, that students have not understood the concept of multiplication because there are still many students who use multiplication boards that they make themselves. The monotonous learning atmosphere also makes students not eager to start learning Mathematics. The pretest results showed that the students' test scores were very low with the percentage of students who scored more than 50 was 32% and from the questionnaire results which showed that students' lack of interest in Mathematics subjects and learning. From the initial data, the researcher designed the Mathemagics method using Ice Cream Math learning media to improve students' understanding of the concept of Mathematics multiplication. Then from the post test results there was an increase in results, namely the percentage of students who scored more than 50 was 96%. So, from the post test results obtained, it is concluded that the use of the Mathemagics method assisted by ice cream math media can improve students' understanding of the concept of multiplication.